Cone-beam computed tomography analysis of the apical third of curved roots after mechanical preparation with different automated systems - Oliveira, Cesar Augusto Pereira (2009)
The present study evaluated by cone-beam computed tomography (CBCT) the apical canal transportation and centralizing ability of different automated systems after root canal preparation. The mesiobuccal canals of maxillary first molars (n=10 per group) were prepared with: GI - reciprocating system with K-Flexofile; GII - reciprocating system with NiTiFlex files; GIII - rotary system with K3 instruments; GIV - rotary system with RaCe instruments. CBCT scans were taken before and after biomechanical preparation up to a #40.02 diameter. Canal transportation was determined by measuring the smallest distance between the inner canal walls and the mesial and distal sides of the root. The centralization ability corresponded to the difference between the measurements from transportation evaluation, using the linear voxel to voxel method of analysis. The mean transportation was 0.06 ± 0.14 mm, with a tendency to deviate to the mesial side of the root (n=22), with no statistically significant difference among the groups (p=0.4153). The mean centralization index was 0.15 ± 0.65 also without statistically significant difference among the groups (p=0.0881). It may be concluded that apical canal transportation and centralization ability were not influenced by the type of mechanical movement and instruments used.